Pengaruh Model Project Based Learning (PjBL) terhadap Kemampuan Berpikir Kritis Siswa Kelas X SMA Negeri 2 Karanganyar Tahun Pelajaran 2012/2013 - Dwi Eka Yanti; Puguh Karyanto; Bowo Sugiharto (BIO-PEDAGOGI, 2013)
This research aimed to find out whether or not there is an effect of Project Based Learning (PjBL) on the critical thinking ability of the X graders of SMA Negeri 2 Karanganyar in biology subject in the school year of 2012/2013. This study was a quasi-experimental research using Post-test Non Equivalent Group Design using cluster sampling. The population of research was all X graders of SMA Negeri 2 Karanganyar in the school year of 2012/2013 consisting of 288 students, while the sample consisted of two classes: control one containing 33 students and experiment one containing 35 students. The control class employed varied lecturing learning method and the experiment one employed Project Based Learning (PjBL) model. Technique of collecting data used was test item and observation sheet. The research hypothesis testing was done using t-test.The result of research showed that Project Based Learning (PjBL) model affected the students’ critical thinking ability. The mean score of critical thinking ability in the experiment class employing Project Based Learning (PjBL) model in learning was higher than that in control class employing varied lecturing method.The conclusion of research was that Project Based Learning (PjBL) model affected significantly the critical thinking ability of the second semester of the X graders of SMA Negeri 2 Karanganyar in the school year of 2012/2013. Key Words: Project Based Learning (PjBL) , critical thinking ability.